Adherence to long‐term supportive periodontal therapy in groups with different periodontal risk profiles. (21st January 2020) - Sonnenschein, Sarah K.; Kohnen, Rebecca; Ruetters, Maurice; Krisam, Johannes; Kim, Ti‐Sun
Abstract: Aim: To examine changes of the periodontal risk assessment (PRA) of patients during long‐term supportive periodontal therapy (SPT) and to examine the adherence to recommended visit intervals. Material and Methods: Retrospective data from 372 SPT patients were evaluated before and after active periodontal therapy (APT) and at least 5 years later. After APT and regularly during SPT, PRA was performed for all included patients (low‐risk/moderate‐risk/high‐risk profile) and they were advised to adhere to 3/6‐/or 12‐month intervals accordingly. The adherence (fully/partially/insufficiently/non‐adherent) to SPT intervals was assessed retrospectively. Results: Initially, 38 patients had a low‐risk, 217 a moderate‐risk and 94 a high‐risk profile. Five years after APT, 55.3% of the low‐risk, 71.9% of the moderate‐risk and 54.3% of the high‐risk patients had not changed their initial risk. 19.5% of the moderate‐risk group shifted to "high‐risk" and 8.6% to "low‐risk". 66% of low‐risk, 34% of moderate‐risk and 13% of high‐risk patients fully adhered to SPT. The portion of non‐adherent patients was the highest within the high‐risk group (18%–43%). The level of adherence was associated with number of lost teeth and mean PPD ( p < .05). Conclusions: Risk profiles can change during SPT. A high level of adherence to SPT intervals based on PRA positively influences the periodontal status.